Thyroid Hormone-Regulated Mouse Cerebral Cortex Genes Are Differentially Dependent on the Source of the Hormone: A Study in Monocarboxylate Transporter-8- and Deiodinase-2-Deficient Mice - Morte, Beatriz (The Endocrine Society, 2010)
Thyroid hormones influence brain development through the control of gene expression. The concentration of the active hormone T(3) in the brain depends on T(3) transport through the blood-brain barrier, mediated in part by the monocarboxylate transporter 8 (Mct8/MCT8) and the activity of type 2 deiodinase (D2) generating T(3) from T(4). The relative roles of each of these pathways in the regulation of brain gene expression is not known. To shed light on this question, we analyzed thyroid hormone-dependent gene expression in the cerebral cortex of mice with inactivated Mct8 (Slc16a2) and Dio2 genes, alone or in combination. We used 34 target genes identified to be controlled by thyroid hormone in microarray comparisons of cerebral cortex from wild-type control and hypothyroid mice on postnatal d 21. Inactivation of the Mct8 gene (Mct8KO) was without effect on the expression of 31 of these genes. Normal gene expression in the absence of the transporter was mostly due to D2 activity because the combined disruption of Mct8 and Dio2 led to similar effects as hypothyroidism on the expression of 24 genes. Dio2 disruption alone did not affect the expression of positively regulated genes, but, as in hypothyroidism, it increased that of negatively regulated genes. We conclude that gene expression in the Mct8KO cerebral cortex is compensated in part by D2-dependent mechanisms. Intriguingly, positive or negative regulation of genes by thyroid hormone is sensitive to the source of T(3) because Dio2 inactivation selectively affects the expression of negatively regulated genes.